Laser assisted fabrication of mechanochemically robust Ti3Au intermetallic at Au-Ti interface - Oktawian Bialas; Augustine N.S. Appiah; Marta Wala; Anil Kunwar; Anna Woźniak; Paweł M. Nuckowski; Wojciech Simka; Peter Råback; Marcin Adamiak (Engineering Science and Technology, an International Journal, 2023)
Intermetallics such as Ti3Au are characterised by improved mechanical properties and reduced susceptibility to corrosion. This study extensively blends the techniques of process simulation by finite element analysis, light microscopy, scanning electron microscopy, energy dispersive spectroscopy and structural roentgenography analysis to investigate the interfacial intermetallics (IMC) in Au-Ti system. Ti was electrochemically coated with a micrometric layer of gold and then laser-treated in a wide range of parameters. Variability included both the laser beam power and the beam feed rate. The experimental results confirm that the formation of an intermetallic Ti3Au phase is possible. Finite element method was employed to numerically estimate the transient temperature values at the Au-Ti interface during laser treatment. At laser power 100 W and scan speed of 1.5 mm/s, the interfacial temperature reached a magnitude larger than the melting point of Ti for a duration less than 5.0 ms. The decrease of scan speed to 1.0 mm/s for constant P, increased this duration up to 97.0 ms where both provided sufficient energy for convection-based reaction at the interface. Through nanoscale molecular dynamics simulation, it has been revealed that during nanoindentation, Ti and Au atoms of Ti3Au IMC exert a larger resistance force to the indenter as compared to the atoms of pure Ti material. The IMC material not only offers a more robust mechanical response during indentation but also exhibits superiority over pure Ti material in a corrosion test.